百度试题 结果1 题目Solve the equation by using the Quadratic Formula. 相关知识点: 试题来源: 解析 You getThe solution of the equation is such that. 反馈 收藏
Solve each equation using the quadratic formula. -4x^2+2x+3=0 相关知识点: 试题来源: 解析 x= (\ 1± √ (13))4 -4x^2+2x+3=0, so a=-4, b=2, c=3.x= (-(2)±√ (2^2-4(-4)(3)))(2(-4))= (-2± √ (52))(-8)= (\ 2± √ 4√ (13))8= (\ 2± 2√ (...
Quadratic Function | Formula, Equations & Examples from Chapter 4 / Lesson 10 141K Learn how to solve quadratic equations. Examine how to use and interpret the quadratic equation formula, and work through examples of solving quadratic equations. Related...
x^2+6x+9=0: 解:x=-3 x^2+7x+10=0: 解:x=-2, x=-5 x^2+4x-21=0: 解:x=-7, x=3反馈 收藏
Tiger shows you, step by step, how to solve YOUR Quadratic Equations t^2+6t+1=0 by Completing the Square, Quadratic formula or, whenever possible, by Factoring
Math Equations Use the quadratic formula to solve the equation. {eq}\displaystyle 4 x^2 - 4 x - 4 = 0 {/eq} Question: Use the quadratic formula to solve the equation. {eq}\displaystyle 4 x^2 - 4 x - 4 = 0 {/eq} Quadratic Formula: The quadratic formula is one o...
To solve a quadratic equation, we can use the ___ formula. A. linear B. quadratic C. cubic D. exponential 相关知识点: 试题来源: 解析 B。解二次方程可以用二次公式,quadratic 是二次的;linear 是线性的;cubic 是三次的;exponential 是指数的。反馈 收藏 ...
Exponents Quadratic Equations Quadratic Formula Chris A. asked • 07/17/17 How to solve this quadratic equation with the quadratic formula? Help?Could someone help me with this question step-by-step using the quadratic formula? 3x² + 24x – 144...
Move ( 5x) to the left side of the equation by subtracting it from both sides. ( 3x^2-5x=0) Use the quadratic formula to find the solutions. ( (-b± √(b^2-4(ac)))/(2a)) Substitute the values ( a=3), ( b=-5), and ( c=0) into the quadratic formula and solve for ...
Move all the expressions to the left side of the equation.( 3x^2+2x-4=0)Use the quadratic formula to find the solutions.( (-b± √(b^2-4(ac)))/(2a))Substitute the values ( a=3), ( b=2), and ( c=-4) into the quadratic formula and solve for ( x).( (-2± √(2^2...